Parental supply of sips and whole drinks of alcohol to adolescents and associations with binge drinking and alcohol-related harms: A prospective cohort study. (1st October 2020) - Aiken, Alexandra; Clare, Philip J.; Boland, Veronica C.; Degenhardt, Louisa; Yuen, Wing See; Hutchinson, Delyse; Najman, Jackob; McCambridge, Jim; Slade, Tim; McBride, Nyanda; De Torres, Clara; Wadolowski, Monika; et al.
Highlights: We found no evidence that parental supply of alcohol has a protective effect. Parental supply of sips associated with increased risks of adverse alcohol outcomes. Supply of larger quantities associated with an increasing risk of adverse outcomes. Abstract: Background: Parents frequently supply alcohol to their children, often only sips. We investigated whether supply of sips and whole drinks, from parents and other sources, are differentially associated with subsequent drinking outcomes. Methods: A cohort of 1910 adolescents (mean age 12.9yrs) were surveyed annually over seven years from 2010−11. We examined prospective, adjusted associations between the quantity of supply from parental and non-parental sources in the preceding 12 months and five outcomes in the subsequent year, over several consecutive years: binge drinking; alcohol-related harms; symptoms of alcohol abuse, dependence and alcohol use disorder (AUD). Results: In early waves, most parental supply comprised sips, while supply of whole drinks increased in later waves. Among those not receiving alcohol from other sources, parental supply of sips was associated with increased odds of binge drinking (OR: 1.85; 99.5 % CI: 1.17–2.91) and alcohol-related harms (OR: 1.70; 99.5 % CI: 1.20–2.42), but not with reporting symptoms of alcohol abuse, dependence or AUD, compared with no supply. Relative to no supply, supply of sips from other sources was associated with increased odds of binge drinking (OR: 2.04; 99.5 % CI: 1.14–3.67) only. Compared with supply of sips, supply of whole drinks by parents or others had higher odds of binge drinking, alcohol-related harms, symptoms of dependence and of AUD. Secondary analysis demonstrated that supply of larger quantities was associated with an increased risk of all outcomes. Conclusion: Parental provision of sips is associated with increased risks and the supply of greater quantities was associated with an increasing risk of adverse outcomes. Clinical Trial Registration: ClinicalTrials.gov (NCT02280551).